KEY SUCCESS FACTORS - Diliza, Nandi (My University, 2011)
Context This research is a study of a Public Private Partnership (PPP) in a South African public hospital using the Inkosi Albert Luthuli Central Hospital in Durban as a case study. An investigation of the challenges facing the PPP as well as the key success factors for this PPP, as expressed by interview respondents, will be determined. Based on findings made in these investigations, a proposal for key success factors for PPPs in South African public hospitals will be made. A brief statement of the problem The researcher has investigated what the challenges are for PPPs in South African public hospitals. Thereafter key success factors for PPPs are determined. The method of data collection In-depth interviews were conducted to elicit responses to the research problems. A set of interview questions were prepared prior to the interviews and were posed to the respondents. This ensured that the interviewer got responses to similar questions so as to be able to get information on the research problems. The key findings Several challenges are facing the PPP being studied. These are a perceived high cost of the PPP as well as doubts about value for money in the partnership. The other challenges are dissatisfaction by some of the managers, on the client’s side, about the functioning of the help desk, response to logged calls and application of the penalty clause. ii Failure by the state to appoint a dedicated, full time, appropriately qualified and skilled contract manager was cited as the main weakness in the management of the PPP. Key success factors of the PPP were that the service provider was in a position to provide the state with a high quality package in all the areas under the PPP; these are Facilities Management, Information Technology and Medical equipment. There had been adequate stakeholder participation during the planning phase of the partnership and even now there are various forums at which the service provider meets with the client at various areas of management and at operational level. The key message PPPs in the South African public sector are a fairly new concept that is providing some lessons to be learnt. Although PPPs provide required capital to enable the state to venture into high value massive public health sector projects, there are challenges facing PPPs and every effort needs to be made to ensure that the challenges and risks are avoided or, at least, mitigated against. Key success factors have been identified in this case study and, ensuring that these are factored into future PPPs in the health sector will definitely assist government in planning and implementing successful partnerships.
MBA - WBS
Keywords: Public private partnerships; Hospitals